Analisis Kualitas Sumber Daya Manusia Terhadap Kinerja Pertumbuhan Ekonomi (Studi Kasus Pada Kegiatan Pelatihan Badan Pengembangan Sumber Daya Manusia Provinsi Papua) - Reveline Octaviani; Mesak Iek; Flora Yvonne de Quelyoe; Risky Novan Ngutra (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2022)
The purpose of this study in full is to analyze the factors of Competence and Performance of Human Resources at the Papua Province Human Resources Development Agency (BPSDM) of Papua Province which have an effect on Papua's economic growth through training activities for the State Civil Apparatus. Descriptive analysis is used to determine the characteristics of respondents and respondents' descriptions of the dimensions of each research variable. In addition, this study uses an analysis of the effect of the quality of human resources on the performance of economic growth. The results of this research show the significant influence of the competence and performance variables of human resources on Papua's economic growth through training activities for the State Civil Apparatus which will be able to increase regional revenues. The findings of this study prove that the level of regional revenue in each period will be influenced by the quality of human resources. And there is a significant positive effect of the Papua Province Human Development Index on Papua's economic growth. Where with the increase in the Human Development Index of each Human Resources will increase the growth of the Papua Province. Based on the results of simultaneous testing, it is known that there is a significant influence on the potential of human resources, performance of human resources, and numbers from the Human Development Index which continue to grow and improve the growth performance of the Papua Province. Keywords: Human Quality, Performance, Economic Growth